Enhancement of bistable nonlinear energy sink based on particle damper. (17th March 2023) - Dou, Jinxin; Yao, Hongliang; Cao, Yanbo; Han, Shengdong; Bai, Ruxue
Highlights: Particle damper (PD) is applied to enhance the performance of the bistable nonlinear energy sink (BNES). The permanent magnet pairs are utilized to generate nonlinear stiffness. The genetic algorithm is employed to guide the parameter design. The good performance of the PDBNES is verified by experimental results. Abstract: To outperform the conventional bistable nonlinear energy sink (BNES), a particle damper bistable nonlinear energy sink (PDBNES) for torsional vibration suppression of rotor systems is designed in this paper. The nonlinear stiffness of the PDBNES is achieved by mutually repulsive magnets, while the nonlinear damping is generated using particle damping technology. Then, the dynamic model of the rotor-PDBNES system is established, and the effect of PDBNES parameters on the equivalent damping coefficient is discussed. Next, the optimization strategies for steady-state response and transient response of the rotor-PDBNES system are proposed, and a comparative study is conducted on the PDBNES and conventional BNES. Finally, the experimental test of the rotor-PDBNES system is carried out, which verifies the ability of the PDBNES to suppress the steady-state vibration of the rotor system. The results show that the vibration suppression performance of the PDBNES is better than that of the conventional BNES. For the steady-state response, the vibration suppression rate of the PDBNES is improved by 15.72% in simulations and 23.23% in experiments. In the transient response, the displacement attenuation speed of the PDBNES is increased by 22.73%, and the efficiency of TET is catalyzed.